2016
DOI: 10.1371/journal.pone.0165827
|View full text |Cite
|
Sign up to set email alerts
|

Identification of In-Chain-Functionalized Compounds and Methyl-Branched Alkanes in Cuticular Waxes of Triticum aestivum cv. Bethlehem

Abstract: In this work, cuticular waxes from flag leaf blades and peduncles of Triticum aestivum cv. Bethlehem were investigated in search for novel wax compounds. Seven wax compound classes were detected that had previously not been reported, and their structures were elucidated using gas chromatography-mass spectrometry of various derivatives. Six of the classes were identified as series of homologs differing by two methylene units, while the seventh was a homologous series with homologs with single methylene unit dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
0
17
1
Order By: Relevance
“…(Sinninghe Damsté et al, 2003;Rampen et al, 2009), and to a lesser extent from A. radians (Rampen et al, 2011), whereas the 1,13-and 1,15-diols are thought to be associated with Eustigmatophyceae (Rampen et al, 2014a, and references cited therein). Previous studies highlighted indeed good correlations in the fluxes of C 28 and C 30 1,14-diols in the water column of the Arabian Sea (Rampen et al, 2007) and the northwestern Indian Ocean (Rampen et al, 2008). Proboscia spp.…”
Section: Comparison Of Diol Distributionsmentioning
confidence: 74%
See 1 more Smart Citation
“…(Sinninghe Damsté et al, 2003;Rampen et al, 2009), and to a lesser extent from A. radians (Rampen et al, 2011), whereas the 1,13-and 1,15-diols are thought to be associated with Eustigmatophyceae (Rampen et al, 2014a, and references cited therein). Previous studies highlighted indeed good correlations in the fluxes of C 28 and C 30 1,14-diols in the water column of the Arabian Sea (Rampen et al, 2007) and the northwestern Indian Ocean (Rampen et al, 2008). Proboscia spp.…”
Section: Comparison Of Diol Distributionsmentioning
confidence: 74%
“…In general, it is thought that 1,13-and 1,15-diols derive from a different source than 1,14-diols in the marine realm (Sinninghe Damsté et al, 2003;Rampen et al, 2007Rampen et al, , 2011. Indeed, linear regressions showed that the concentration of the C 30 1,15-diol is significantly correlated with those of the C 30 1,13-and C 32 1,15-diols ( Fig.…”
Section: Comparison Of Diol Distributionsmentioning
confidence: 95%
“…For example, many cereal crop species have high concentrations of β‐diketones in their waxes (von Wettstein‐Knowles, ). In this context, wheat waxes have been investigated in much chemical detail, revealing substantial variation between different cultivars, organs, and growth stages (Racovita et al, ; Racovita & Jetter, ; Racovita & Jetter, ). Further research suggested that wax alkanes accumulated mostly in the heading and later stages of wheat development, in particular on flag leaf blades, peduncles, and spikes (Wang et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[14] Cuticular waxes are complex mixtures of very-long-chain (VLC, > C 20 ) saturated aliphatic compounds, bearing no functionality or only one functional group at one end of the carbon chain (hence a primary functionality). [15] Most commonly encountered are homologous series of even-numbered fatty acids, primary alcohols, alkyl esters and aldehydes, as well as odd-numbered alkanes, secondary alcohols and ketones. [13,16] In the wax mixtures of some plant species, alicyclic compounds (e. g., diterpene acids, hydroxy diterpenes, triterpenoids) and aromatic compounds (e. g., alkylresorcinols) may also be quite abundant.…”
Section: Introductionmentioning
confidence: 99%